2020
DOI: 10.13106/jafeb.2020.vol7.no7.463
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Stock Markets: An Empirical Analysis of World Major Stock Indices

Abstract: This study aims to investigate the impact of COVID-19 pandemic on the stock markets of sixteen countries. Pooled OLS regression, conventional t-test and Mann-Whitney test are used to estimate the results of the study. We construct a weekly panel data of COVID-19 new cases and stock returns. Pooled OLS estimation result shows that the growth rate of weekly new cases of COVID-19 negatively predicts the return in stock market. Next, the returns on leading stock indices of these countries during the COVID-19 outbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
1
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(167 citation statements)
references
References 14 publications
14
130
1
22
Order By: Relevance
“…Using daily COVID-19 confirmed cases and deaths, he found that stock markets responded negatively to increases in COVID-19 confirmed cases. Liu et al ( 2020 ) and Khan et al ( 2020 ) used econometric models to evaluate the short-term impact of the coronavirus outbreak on major affected countries’ stock market indices. Results showed that stock markets fell quickly after the virus outbreak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using daily COVID-19 confirmed cases and deaths, he found that stock markets responded negatively to increases in COVID-19 confirmed cases. Liu et al ( 2020 ) and Khan et al ( 2020 ) used econometric models to evaluate the short-term impact of the coronavirus outbreak on major affected countries’ stock market indices. Results showed that stock markets fell quickly after the virus outbreak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since investors anticipated the lockdown, they reacted positively, however, in the pre-lockdown period investors panicked with negative AAR. Khan et al (2020) investigates the impact of COVID-19 pandemic on the stock markets of 16 countries using pooled OLS regression, conventional t-test and Mann-Whitney test. Pooled OLS estimation result shows that the growth rate of weekly new cases of COVID-19 negatively predicts the return in stock markets.…”
Section: Covid-19 Impact On Stock Marketsmentioning
confidence: 99%
“…Prinsip penciptaan kekayaan dalam keuangan sebagian besar didasarkan pada gagasan pembayaran dividen dan kenaikan harga saham (Majanga, 2015 Kondisi darurat seperti adanya bencana alam maupun pandemic, seringkali memengaruhi perilaku investor yang akhirnya memengaruhi harga saham (He et al, 2020). Dengan adanya kondisi pandemi COVID-19 memperburuk situasi jika bank gagal memenuhi kebutuhan pembiayaan perusahaan karena terjadi penurunan permintaan tibatiba dan akhirnya berdampak pada jatuhnya pasar saham di seluruh dunia (Khan et al, 2020). Perubahan harga saham saat pandemi bisa terjadi dikarenakan pengeluaran konsumen tertekan lalu perusahaan menurunkan prospek pendapatan mereka yang berdampak pada penilaian ulang pasar terhadap nilai perusahaan dan jatuhnya harga saham yang besar (Mazur et al, 2020).…”
Section: Harga Sahamunclassified